Phase II study of nab-paclitaxel with gemcitabine for relapsed/refractory small cell lung cancer - Byrne, Margaret M.; Sutamtewagul, Grerk; Zeitler, William; Mott, Sarah L.; Zamba, Gideon K.D.; Kojadinovic, Arsenije; Zhang, Jun; Abu-Hejleh, Taher; Clamon, Gerald; Furqan, Muhammad (Frontiers in Oncology, 2024)
Background: Patients with small cell lung cancer (SCLC) often respond to first-line chemoimmunotherapy. However, relapse is inevitable and is associated with a poor prognosis.Treatments for relapsed SCLC, such as lurbinectedin and topotecan, are limited by modest efficacy and significant hematologic adverse events, leaving a need for newer therapeutic agents or regimens. The combination of gemcitabine and nab-paclitaxel is active and safe in other types of malignancies, such as pancreatic cancer.We conducted a phase II trial evaluating the efficacy and safety of gemcitabine and nab-paclitaxel in patients with relapsed/refractory SCLC. The primary endpoint was objective response rate (ORR), defined as the proportion of patients with confirmed complete or partial response.Secondary endpoints included time to progression (TTP), progression-free survival (PFS), overall survival (OS), and safety.Between October 2016 and May 2021, 32 patients were enrolled. Patients were followed for a median of 9.3 months (range 1.8-65.2). Median age was 65 years (range 48-81). Fifty percent of patients were female. Fifty-three percent of patients had platinum-resistant/refractory relapsed SCLC. The ORR was 28.1% (95% confidence interval [CI] 15.5-100%). Median PFS was 2.9 months (95% CI 2.4-3.6), and median OS was 9.3 months (95% CI 5.2-12.4). Seven patients (21.9%) developed grade 3 or 4 neutropenia.Our study showed that the combination of gemcitabine and nab-paclitaxel led to encouraging outcomes in relapsed/refractory SCLC. Further studies are needed to compare this combination with other treatments used for relapsed SCLC, including lurbinectedin, temozolomide, and topotecan.